Simulation of the electronic states in the band gap for ZnS: Cu, Cl crystallophosphors - Savchenko, N.D.; Shchurova, T.N.; Popovych, K.O.; Rubish, I.D.; Leising, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The results of calculations of the valence band top, conduction band bottom, optical band gap, gap states formed by the homopolar bonds and clusters in ZnS: Cu, Cl crystallophosphors have been presented. The calculation procedure has been based on the linear combination of atomic orbitals and pseudo-potential methods. The energy values have been determined in the centre of the Brillouin zone. The atomic terms determined within Herman-Skillman and Hartree-Fock approximations have been used in the calculations. The quantitative agreement between theoretical and experimental data on the band gap and photoemission threshold for this type of materials has been shown. The energy values for the optical transitions have been determined (1.77; 2.41; 2.65 and 2.95 eV) and correlated with the experimental emission spectra for the samples processed under different conditions.